1993
DOI: 10.1002/hrm.3930320211
|View full text |Cite
|
Sign up to set email alerts
|

360‐degree feedback as a competitive advantage

Abstract: This article examines the status of 360‐degree feedback in organizations. How to optimally use feedback from multiple constituencies as a competitive advantage is discussed. Differences between traditional performance appraisal and 360‐degree feedback are elucidated. Elements of designing and implementing an effective 360‐degree feedback program are explored: content, employee involvement, item type, format, relevance, implementation, using results for evaluation and/or development, including managers' self‐as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
157
1
5

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(165 citation statements)
references
References 20 publications
2
157
1
5
Order By: Relevance
“…As managerial jobs become more complex and multidimensional (London & Beatty, 1993;Varma, Beatty, Schneier, & Ulrich, 1999), organizations are increasingly implementing high-performance work practices such as 360-degree feedback interventions in hopes of improving workplace attitudes and performance (Atwater, Waldman, & Brett, 2002;London, 1997;London & Smither, 1995;Tornow & London, 1998). A very recent large survey found that about one in five firms currently use 360s (Armour, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…As managerial jobs become more complex and multidimensional (London & Beatty, 1993;Varma, Beatty, Schneier, & Ulrich, 1999), organizations are increasingly implementing high-performance work practices such as 360-degree feedback interventions in hopes of improving workplace attitudes and performance (Atwater, Waldman, & Brett, 2002;London, 1997;London & Smither, 1995;Tornow & London, 1998). A very recent large survey found that about one in five firms currently use 360s (Armour, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Practitioners and organizational consultants, based on their experiences with clients, firmly believe that multi-rater or 360-degree feedback systems enhance self-knowledge and consequently improve managerial behavior (Hazucha, Hezlett & Schneider, 1993;London & Beatty, 1993). Scholarly research has confirmed these sentiments and found that higher levels of congruence between managerial "self" and "total others" behavioral ratings is associated with managerial effectiveness and performance (Atwater & Yammarino, 1992;Van Velsor, Taylor & Leslie, 1993;Church, 1997).…”
Section: Feedback: Self/total Others Discrepancy Using Eci 10mentioning
confidence: 99%
“…The objectives of the 360 degree feedback could be blurred if linked with the financial incentives and it could diverge it towards performance appraisal. Thus, it helps in building the leadership and management qualities in the employee and contributing towards organizational growth (London & Beatty, 1993).Therefore, organizational culture and behavior become more adaptive to administering the 360 degree feedback regularly.…”
Section: -Degree Feedback: Employee and Organization Growth:-mentioning
confidence: 99%